LENGTH-WEIGHT RELATIONSHIP AND DIET OF Gymnarchus niloticus IN A TROPICAL MAN-MADE LAKE, SOUTHWESTERN NIGERIA - AYOADE, A.A.; MUSTAPHA, A.T.; OGUNTOLU, M.O. (Nigerian Journal of Fisheries, 2013)
The trunk fish, Gymnarchus niloticus (Family Gymnarchidae) is endemic to Africa. This study reports the length – weight relationship (LWR) and food habit of 108 specimens of G. niloticus in Eleiyele Lake, Ibadan Nigeria were investigated. The LWR of the species showed positive correlation (r > 0.67). The regression exponent (b < 3) for the combined specimens showed negative allometric growth pattern. Variations were recorded in the b value with months and size groups. The mean condition factor (K) was 0.231 ± 0.01. Significant variation occurred in K with size groups and the smallest size group recorded the highest value (0.225 ± 0.01). Diet evaluated with the Index of Relative Importance (IRI) showed that G.niloticus primarily consumed fish (94.9%).